ANALYSIS OF INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY TO THE REPURCHASE INTENTION MEDIATED BY TRUST IN MS GLOW FOR MEN PRODUCTS - Zaela Okta Widyastuti; Dwi Suryanto Hidayat (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
In an online business, the interaction between consumer and seller is limited which causes consumerto only give the rating of the quality of a product. The existence of repurchase interest will happen if the seller improves the quality of his product, so, it can be possible for customers to repeat purchases. This study was conducted to analyze the effect of brand image and product quality on repurchase intention using trust as a mediation. The used sample for this research was 96 respondents, which male consumers who use MS Glow For Men cosmetic products that live in Central Java, also consumers who purchase the products through the Shopee application at least twice. This research is a quantitative research. The sampling technique in this research is purposive sampling with non-probability sampling technique. The process of calculating data in this study uses SmartPLS. The results showed that brand image has a significant effect on repurchase intention, but brand image does not have a significant effect on repurchase intention through trust mediation, product quality has a significant influence on repurchase intention and trust, but product quality does not have a significant effect on repurchase intention through trust